Elevated Expression and Pro-Inflammatory Activity of IL-36 in Patients with Systemic Lupus Erythematosus - Chu, Man; Wong, Chun; Cai, Zhe; Dong, Jie; Jiao, Delong; Kam, Ngar; Lam, Christopher; Tam, Lai (Molecules (Basel, Switzerland), 2015)
We investigated the expression and proinflammatory activity of interleukin (IL)-36 in patients with systemic lupus erythematosus (SLE). The expression level of IL-36, its putative receptors and the frequency of CD19+CD24highCD27+ regulatory B (Breg) lymphocytes of peripheral blood from 43 SLE patients and 16 normal control (NC) subjects were studied using ELISA and flow cytometry. Plasma cytokines/chemokines and ex vivo productions of cytokine/chemokine from peripheral blood mononuclear cells (PBMC) stimulated with recombinant IL-36 were determined by Luminex multiplex assay. Plasma concentrations of IL-36α, IL-36γ and the proportions of circulating IL-36R-positive CD19+ B lymphocytes in total B lymphocytes and PBMC were significantly increased in active SLE patients compared with NC (all p < 0.05). Plasma IL-36α and IL-36γ correlated positively with SLE disease activity and elevated plasma IL-10 concentration (all p < 0.05). The frequencies of circulating Breg lymphocytes in total B lymphocytes and PBMC were significantly decreased in both inactive and active SLE patients compared with NC (all p < 0.01). The frequency of Breg lymphocytes in total B lymphocytes correlated negatively with the proportion of IL-36R-positive B lymphocytes (p < 0.05). IL-36α exerted substantial proinflammatory effect in PBMC from SLE patients by inducing the production of IL-6 and CXCL8. Upon stimulation with IL-36α and IL-36γ, ex vivo productions of IL-6 and CXCL8 were significantly increased in SLE patients compared with NC (all p < 0.05). This cross-sectional study demonstrated that over expression of circulating IL-36α may exert a proinflammatory effect as observed in human SLE.